International Mycological Congress: Guiding Vote on nomenclature proposals to amend Chapter F of the International Code of Nomenclature for algae, fungi, and plants - Tom W. May; Andrew N. Miller (IMA Fungus)
Abstract Results are provided for the Guiding Vote on the seven formal proposals to amend the International Code of Nomenclature for algae, fungi, and plants to be decided by the Fungal Nomenclature Session (FNS) of the XI International Mycological Congress in July 2018. Te ballot for the Guiding Vote was provided online. Tere were 520 valid ballots, submitted by mycologists from 42 countries, belonging to 23 eligible groups and societies, along with authors of proposals. Tw o proposals F-005 and F-006, both concerning DNA sequences as types, exceeded the 75 % No vote that is the threshold above which proposals are considered rejected by the FNS unless formally re-introduced. Two options for amendments to future procedures for the Guiding Vote are proposed: adding eligibility via publication of a nomenclatural novelty among fungi and removing eligibility via membership of IMA MMOs.